SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK PADA SMK ISLAM AL-ARIEF MUARO JAMBI - Faiza Rini (JURNAL AKADEMIKA)
The difficulty of access to know the best teachers in one school resulted in schools are under enormous pressure to determine how to optimize its resources. Selection of a suitable best teachers play an important role in this regard. This study aims to determine the best teachers, with some alternative way of selecting the best teacher positions based on selection criteria that have been set previously. Problems in the selection of the best teachers is difficult to determine the best teachers based on many of the criteria. Another problem is that not all criteria can be measured quantitatively. Fuzzy Multi Attribute Decision Making (FMADM) is a method used to find the optimal alternative of a number of alternatives to certain criteria. The essence of FMADM is to determine the weight values for each attribute, followed by the ranking process that will select the alternatives that have been granted using Borland Delphi applications.